A whole‐body circulatory neutrophil model with application to predicting clinical neutropenia from in vitro studies - Wenbo Chen; Britton Boras; Tae Sung; Wenyue Hu; Mary E. Spilker; David Z. D'Argenio (Wiley, 2021)
Abstract A circulatory model of granulopoiesis and its regulation is presented that includes neutrophil trafficking in the lungs, liver, spleen, bone marrow, lymph nodes, and blood. In each organ, neutrophils undergo transendothelial migration from vascular to interstitial space, clearance due to apoptosis, and recycling via the lymphatic flow. The model includes cell cycling of progenitor cells in the bone marrow, granulocyte colony‐stimulating factor (G‐CSF) kinetics and its neutrophil regulatory action, as well as neutrophil margination in the blood. From previously reported studies, 111In‐labeled neutrophil kinetic data in the blood and sampled organs were used to estimate the organ trafficking parameters in the model. The model was further developed and evaluated using absolute neutrophil count (ANC), band cell, and segmented neutrophil time course data from healthy volunteers following four dose levels of pegfilgrastim (r2 = 0.77-0.99), along with ANC time course responses following filgrastim (r2 = 0.96). The baseline values of various cell types in bone marrow and blood, as well as G‐CSF concentration in the blood, predicted by the model are consistent with available literature reports. After incorporating the mechanism of action of both paclitaxel and carboplatin, as determined from an in vitro bone marrow studies, the model reliably predicted the observed ANC time course following paclitaxel plus carboplatin observed in a phase I trial of 46 patients (r2 = 0.70). The circulatory neutrophil model may provide a mechanistic framework for predicting multi‐organ neutrophil homeostasis and dynamics in response to therapeutic agents that target neutrophil dynamics and trafficking in different organs.